1978
DOI: 10.1007/bf02010744
|View full text |Cite
|
Sign up to set email alerts
|

Failure of heterotopic osteogenesis by epithelial mesenchymal cell interactions in xenogeneic transplants in the kidney

Abstract: Transitional epithelium of the guinea pig and rabbit and an established WISH cell line, when grafted under the kidney capsule of cortisone treated mice, survived and proliferated, but never induced bone formation. On the contrary, when grafted intramuscularly into the same recipients, readily induced cartilage and/or bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…it has been observed that early muscle progenitors called muscle stem cells exist within skeletal muscle (35). The current data add further circumstantial evidence to the findings of Wlodarski (63,64), supporting an interrelationship between myoprogenitor and osteoprogenitor cells.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…it has been observed that early muscle progenitors called muscle stem cells exist within skeletal muscle (35). The current data add further circumstantial evidence to the findings of Wlodarski (63,64), supporting an interrelationship between myoprogenitor and osteoprogenitor cells.…”
Section: Discussionsupporting
confidence: 82%
“…Urist et al hypothesized that the endomysium was an important source of mesenchymal cell5 acting as osteoprogenitor cells (5536). Similar implantation studies using transitional epithelium demonstrated bone induction when grafted into skeletal muscle but not under the renal capsule (63). On the be used in models testing cell-based gene therapy.…”
Section: P Boscii E T Rlmentioning
confidence: 91%
See 1 more Smart Citation
“…However, more recent data examining the role of epithelial cells in the development of HO have shown that these cells are likely to have only a minor and indirect role in HO. For instance, when cultured with mesenchymal cells of the mouse thigh or intramuscularly implanted, osteochondrogenic differentiation was observed [74]. However, in this study it was not reported whether it was the epithelial cell population or local mesenchymal cells within the muscle that contributed to the resultant osteogenic population.…”
Section: Ectoderm Epithelial Cellsmentioning
confidence: 62%
“…Currently, the cross-differentiation from cells of one germ layer to another is gaining much attention as a process involved in the initiation of HO. However, the osteogenic potential of epithelial cells is subject to much debate, with some studies demonstrating an osteogenic potential while others refute it [74,75]. Early experiments looking into the effects of transplanting urinary transitional epithelium into the connective tissues of dogs and rabbits demonstrated the formation of mineralised tissue [76], while more recent studies have shown that epithelial cells over-express factors required for osteochondrogenic differentiation such as TGF-β and BMP-2 during their proliferative phase, and as such may exert a paracrine effect during HO pathogenesis [77].…”
Section: Ectoderm Epithelial Cellsmentioning
confidence: 99%